1982
DOI: 10.2134/agronj1982.00021962007400020014x
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Yield Components of Four Spring Wheat Cultivars Grown Under Three Tillage Systems1

Abstract: Soil erosion is a serious problem in the wheat (Triticum aestivum L.) producing areas of the Palouse Region of the Pacific Northwest. A field study was conducted under three environmental conditions [a Palouse silt loam (Pachic Ultic Haploxerolls, fine‐silty, mixed, mesic) during 1980 and an Athena silt loam (Pachic Haploxerolls, fine‐silty, mixed, mesic) during 1979 and 1980] to determine the effects of three tillage systems on grain yield and yield components of four soft white spring wheat cultivars, WS‐1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
27
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 6 publications
7
27
1
Order By: Relevance
“…Similar to the first year of the experiment, significant differences were found among tillage treatments in the third year and the DD treatment provided the highest yield compared with other treatments. Grain yield ranking from the highest to the lowest was ST > DD > CT when averaged across years, indicating that grain production increased as tillage decreased, similar to the findings of others (Ciha, 1982;Cantero-Martínez et al, 2003;Patrick et al, 2003). This study's finding is also consistent with Carter (1991), who found that shallow tillage removed some of the constraints associated with direct drilling and provided an alternative to mouldboard ploughing.…”
Section: Tillage Effects On Wheat Grain Yieldsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to the first year of the experiment, significant differences were found among tillage treatments in the third year and the DD treatment provided the highest yield compared with other treatments. Grain yield ranking from the highest to the lowest was ST > DD > CT when averaged across years, indicating that grain production increased as tillage decreased, similar to the findings of others (Ciha, 1982;Cantero-Martínez et al, 2003;Patrick et al, 2003). This study's finding is also consistent with Carter (1991), who found that shallow tillage removed some of the constraints associated with direct drilling and provided an alternative to mouldboard ploughing.…”
Section: Tillage Effects On Wheat Grain Yieldsupporting
confidence: 87%
“…Among yield components, only thousand kernel weight showed no significant effect due to tillage. Some authors observed a similar response to tillage (Arshad et al, 1994;Patrick et al, 2003), whereas others reported that kernel weight increased as tillage declined (Ciha, 1982). Similarly, Galantini et al (2000) concluded that there was no significant difference on kernel weight in a wheat-vetch rotation.…”
Section: Tillage Effects On Wheat Yield Componentsmentioning
confidence: 90%
“…For example, the relative ranking of four soft white spring wheat cultivars across three tillage systems changed for grain yield in the U.S. Pacific Northwest, prompting the recommendation that cultivars must be developed for specific tillage environments (Ciha, 1982). For example, the relative ranking of four soft white spring wheat cultivars across three tillage systems changed for grain yield in the U.S. Pacific Northwest, prompting the recommendation that cultivars must be developed for specific tillage environments (Ciha, 1982).…”
mentioning
confidence: 99%
“…Differences among wheat cultivars both across and possibly within studies may contribute to the inconsistency in yield response to changes in tillage. For example, the relative ranking of four soft white spring wheat cultivars across three tillage systems changed for grain yield in the U.S. Pacific Northwest, prompting the recommendation that cultivars must be developed for specific tillage environments (Ciha, 1982). A similar recommendation resulted when cultivars were compared in tilled and untilled environments in South Dakota (Hall and Cholick, 1989).…”
mentioning
confidence: 99%
“…Kernel weight increased for soft white spring wheat as tillage declined in a continuous small-grain system at 2 out of 3 locations in the Pacific Northwest (Ciha, 1982). This researcher attributed the increase in kernel weight to the moisture conservation benefits that resulted from maintaining crop residue on the surface under reduced tillage and NT compared with CT systems.…”
Section: Discussionmentioning
confidence: 99%